Face masks invading protected areas: Risks and recommendations - Dioses-Salinas, Diana Carolina; Pizarro-Ortega, Carlos Ivan; Dobaradaran, Sina; Ben-Haddad, Mohamed; De-la-Torre, Gabriel Enrique (The Science of the total environment, 2022)
Among the indirect environmental impacts generated by the global COVID-19 pandemic, contamination with personal protective equipment (PPE), like face masks, may be one of the most relevant ones. PPE has been found in multiple aquatic, marine, and terrestrial environments, including places of absolute relevancy to biodiversity conservation, such as protected areas (PAs). Here, a brief report of the presence of PPE in six PAs of Peru is presented. PPE pollution in PAs consisted mainly of single-use and reusable face masks, as well as plastics associated with PAs, such as KN95 respirator wrappings. The mean PPE density was estimated as 1.32 × 10−3 PPE/m2. FTIR spectroscopy confirmed that face masks and wrappers mainly consisted of polypropylene and polyethylene, two of the most commonly available synthetic polymers. The material was poorly degraded according to their FTIR spectra, possibly suggesting that they were discarded recently. The recent ban on single-use plastic in Peruvian PAs is regarded as a great step forward toward the efforts made to preserve these invaluable places. However, these measures seemed insufficient to prevent PPE and other types of litter from contaminating areas of ecological importance. Considering the current scenario, several recommendations were proposed to be implemented in PAs in order to prevent PPE from becoming a new plastic issue to tackle. These recommendations are expected to also serve for future events where the use of single-use plastics becomes inevitable, like global pandemics. [Display omitted] •Protected areas (PAs) are subject to personal protective equipment (PPE) pollution.•Tourism is the main driver of PPE pollution in PAs.•PPE releases secondary contaminants and poses entanglement hazards.•Management recommendations for the current and future scenarios are provided.